Os Xukuru-Kariri e as elites: história, poder e conflito territorial em Palmeira dos Índios – AL (1979-2015) - Santos, Luan Moraes dos (2019)
The objective of this work is the analysis of the relations of domination and insertion of the political elites and indians in the power disputes listed in the process of demarcation of lands in the municipality of Palmeira dos Índios - AL, between 1979 (year of resumption of the Mata da Cafurna region) and 2015 (when the MPF determined the demarcation). The development of research in the field of indigenismo has been gaining form in the last years, with approaches that consider the Indians active in the present day. This research considers the continuities and ruptures of the Indians tradition in the current historical process; contextualizing their claims, affirmation needs and recognition of the interests of local and regional opposition forces. It points out a relevant work from the historiographic point of view to understand the interfaces of the development of the history of Alagoas, since the presence of Indians in all regions of the state is present, proving that we live with territorial retakes and the political tensions that surpass the official history are present when we observe that the organization of Indians movements since the second half of the twentieth century, as opposed to the agreement of squatters and invaders of the territories currently targeted in the process of land demarcation in the region. FUNAI reports and indigenist entities; photographs, field diaries and transcribed interviews to possess a collection of primary sources, such as the Luiz Byron Torres collection, which contains texts not yet published and little known by the public. So, a methodology of analysis is used that dialogues with John Pocock (2003) to clarify the language and its social representations present in the content of political acts. And to trace the networks of social tension, as well as the power relations that are related to the practices of domination in the territorial dispute, we refer to Michael de Certeau (2011). Thus, to understand the interests of the electors as a form of power, it uses the theoretical assumptions indicated by Boaventura de Souza Santos (1999). In addition, to understand the experiences of Indians with struggles as coherent groups, organized around rituals and procedures, we use the concepts of tradition bequeathed by Eric Hobsbawm (1998), as well as the conceptualization of the imagined community in Benedict Anderson (2008). In order to re-signify the historical process experienced by the Indians of the Northeast, we study their cultural reform, starting from the initial fact of the mixture and new cultural elaboration defended by João Pacheco de Oliveira (1998), also the resurgence signs enumerated by José Maurício Arruti (1999) and Siloé Amorim (2003). The dissertation under that allows for reflections with support in the relations of local political power that relate strategies of domination, struggles and resistance between Indians and landowners/ squatters.